Postpartum administration of PGF2α and reproductive performance in timed artificial insemination of beef cows - Tamires Korchovei Sanches; Rafaela Schoma Cardoso; Marcio de Oliveira Marques; Rubens Cesar Pinto da Silva; Luiz Francisco Machado Pfeifer; Amanda Fonseca Zangirolamo; Fábio Morotti; Marcelo Marcondes Seneda (Semina: Ciências Agrárias)
This study aimed to evaluate the effect of prostaglandins on the proportion of inflammatory cells (PMN) and postpartum pregnancy rates in cows subjected to fixed-time artificial insemination (FTAI) programs. In total, 209 postpartum Nelore cows were used in this study. Females were separated into three groups to receive the following treatments: control group- CTL (n = 66), females that were not treated; group 0.5 PG (n = 68), cows that received cloprostenol 0.5mg – a PGF2α analog; and group 1.0 PG (n = 75), cows that received 1mg of cloprostenol. All females were subjected to the FTAI protocol at an average of 38.7 ± 7.6 (Mean ± SD) days postpartum (DPP). Uterine health was assessed using polymorphonuclear cell (PMN) counts. On Day 0 of the FTAI protocol (D0), material was collected using disposable cervical brushes for cytology and analysis of the proportion of inflammatory cells (PMN) recovered from the endometrium in the cervical region. Pregnancy diagnosis was performed by transrectal ultrasonography 30 days after FTAI. Logistic regression was used to analyze the effects of treatment, category, and their interactions on Pregnancy/Artificial Insemination (P/AI). The proportion of PMN cells according to the group was analyzed using ANOVA (PROC GLIMMIX; SAS Inst. Inc., Cary, NC, USA), and the means were compared between groups using Tukey’s test. A level of 5% was considered significant. The proportion of PMN did not differ among the groups. The overall pregnancy rate was 72.2% (151/209). No effects of group (P = 0.51) or category (P = 0.84) were detected on the P/AI among the groups. There was a tendency (P = 0.07) for a group-category interaction for P/AI. In this regard, the P/AI in multiparous cows treated with 1mg of PGF2α tended to be higher (P = 0.08) than that in the control cows.